Adaptively reconstructing network of soft elastomers to increase strand rigidity: towards free-standing electro-actuation strain over 100%. Issue 10 (6th September 2021) - Chen, Zheqi; Ma, Zipeng; Tang, Jiali; Xiao, Youhua; Mao, Jie; Cai, Yiting; Zhao, Junjie; Gao, Xiang; Li, Tiefeng; Luo, Yingwu
Abstract : A thermomechanical training method is reported to increase the network strand rigidity of triblock copolymer elastomers, leading to significantly enhanced electro-actuation performance. Abstract : Soft biological tissues and muscles composed of semiflexible networks exhibit rapid strain-hardening behaviors to protect them from accidental rupture. In contrast, synthetic soft elastomers, usually featuring flexible networks, lack such behaviors, leading to a notorious issue when applying them to a promising artificial muscle technology (dielectric elastomer, DE), that is electromechanical instability (EMI) induced premature breakdown. We report that a facile thermomechanical training method can adaptively reconstruct the network of a soft triblock copolymer elastomer to transform its flexible network strands into semiflexible ones without extra chemical modifications and additives so that the electro-actuation performance is significantly enhanced by avoiding EMI. The free-standing actuators of trained elastomers exhibit a large stable electro-actuation strain and a high theoretical energy density (133%, 307 kJ m −3 at 158.1 V μm −1 ), and the capacity of actuating at low-temperature environments (−15 °C).